2020
DOI: 10.1371/journal.pone.0231768
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing moral hazard from access for high-cost healthcare under insurance

Abstract: Health policy has long been preoccupied with the problem that health insurance stimulates spending ("moral hazard"). However, much health spending is costly healthcare that uninsured individuals could not otherwise access. Field studies comparing those with more or less insurance cannot disaggregate moral hazard versus access. Moreover, studies of patients consuming routine low-dollar healthcare are not informative for the high-dollar healthcare that drives most of aggregate healthcare spending in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…17 It has been shown that the existence of readily available free care shifts individuals' behavior. 15,16 In general, the characteristics of those who opt to delay the procedure for either TKA or THA are as follows: Individuals who delay are more likely to be female and non-Hispanic White, have a lower functional status, be discharged to a nonhome facility, and have a longer LOS. Interestingly, those older than 65 years undergoing THA were more likely to have an ASA class of .3, but this was not notable in those undergoing TKA or the combined group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 It has been shown that the existence of readily available free care shifts individuals' behavior. 15,16 In general, the characteristics of those who opt to delay the procedure for either TKA or THA are as follows: Individuals who delay are more likely to be female and non-Hispanic White, have a lower functional status, be discharged to a nonhome facility, and have a longer LOS. Interestingly, those older than 65 years undergoing THA were more likely to have an ASA class of .3, but this was not notable in those undergoing TKA or the combined group.…”
Section: Discussionmentioning
confidence: 99%
“…13 - 15 In medicine, moral hazard is used to state that the availability of health insurance increases spending. 16 Classically, it states that individuals consume care indiscriminately because they are sheltered from its financial implications. It has been explored through differences in emergency department utilization in teenagers after ineligibility of their parents' health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral hazard has preoccupied health economics and U.S. health policy for half a century (8). When Medicare providers' payment patterns changed to a prospective Diagnostic Related Groups (DRG) system in the United States, hospitals raised the patient's disease code to a higher level (up-coding).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the management of medical resources, it has become clear that adherence to medication and moral hazards among patients are closely related to clinical outcomes and have a significant impact not only on health behaviours but also on socioeconomic factors, including medical costs [ 10 , 11 ]. Improvements in medication adherence have been reported to reduce the economic burden as well as the burden of chronic disease on patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%